Laparoscopic Adnexal Detorsion in a 20-Week Pregnant Patient: A Case Report and Literature Review - Rawad Halimeh; Serge Tomassian; Maria El Hage; Nicole Metri; Marianne Bersaoui; Rafi Daou; Elie Anastasiadis (Case Reports in Obstetrics and Gynecology)
Adnexal torsion is a cause of severe pelvic pain in reproductive aged women and during pregnancy. Adnexal torsion occurs when there is a complete turn of the ovary, tube, or both resulting in impaired blood flow to the ovary. The diagnosis of adnexal torsion is sometimes challenging due to the enlarged effect of the uterus, the displacement of abdominal and pelvic structures and the nonspecific symptoms in pregnancy. Therefore, prompt diagnosis is essential for better maternal and neonatal outcomes. The gold standard for confirmation and treatment of ovarian torsion is surgery. Laparoscopy and Laparotomy are surgical options with defined risks and benefits. Therefore, choosing the best surgical technique and surgical procedure are of utmost importance to decrease the chances of adverse events intra and postoperatively. Little literature exists regarding the laparoscopic approach of an ovarian torsion during the second trimester. Our case is a 20-week pregnant patient who had a 1080 degree rotation of the left adnexa. She required laparoscopy for adnexal detorsion and had good intraoperative, postoperative, maternal, and neonatal outcomes following management.